UNREVALING THE JOINT IMPACT OF PARENTAL SUPPORT, SCHOOL ENVIRONMENT, AND TEACHER MORALE ON STUDENT LEARNING ACHIEVEMENT - Werang, Basilius Redan; Susiani, Ketut; Yudiana, Kadek; Widiastuti, Ni Putu Kusuma; Pio, Riane Johnly; Asaloei, Sandra Ingried; Jim, Edmond Leonard (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Global educational practitioners and policymakers consider student learning outcomes as a pressing concern. In this regard, the joint activities of the school, the parents, and the educators are highly important to the student’s academic success. This research aims to investigates the simultaneous effects of parental involvement, school climate, and teacher morale on student learning achievement. For this purpose, a quantitative method was applied through a survey research design. Out of 10 suburban elementary schools in Buleleng District, a sample of 219 fifth graders were estahlished. The instruments related to parental support, school environment, and teacher’s morale were used in three different questionnaires, whereas the information about student learning achievement was acquired through their academic transcripts. The detailed obtained data were analyzed using inferential statistical methods with the SPSS version 21 software program. The result has shown that parental support, school environment, and teacher morale simultaneously affect the student’s learning achievement. This finding underscores that a child’s performance depends on integrating different factors. Creating and maintaining collaborative networks is essential for driving change in educational settings. This collaboration plays a vital role in supporting all aspects of a child’s development—cognitive, emotional, and social. At the outset, parents provide valuable insights into their child’s strengths, challenges, and learning preferences. This information enables teachers to adapt their teaching strategies to better suit each child’s unique needs, resulting in a more effective and personalized learning experience.